2008
DOI: 10.1530/rep-07-0529
|View full text |Cite
|
Sign up to set email alerts
|

Leydig cell re-generation and expression of cell signaling molecules in the germ cell-free testis

Abstract: Leydig cells in the rat testis can be specifically ablated with ethane dimethane sulfonate (EDS) and will subsequently re-generate. In this study, we have characterized Leydig cell re-generation and expression of selected cell-signaling molecules in a germ cell-free model of EDS action. This model offers the advantage that re-generation occurs on a stable background without confounding changes from the regressing and repopulating germ cell population. Adult rats were treated with busulfan to remove the germ ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 34 publications
3
55
0
2
Order By: Relevance
“…Cells on the tubule surfaces first underwent division, and then differentiated and produced T (17). These results suggested that in addition to reported perivascular locations in the interstitial compartment (18), stem cells also were located on the surfaces of the seminiferous tubules (16,19,20).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Cells on the tubule surfaces first underwent division, and then differentiated and produced T (17). These results suggested that in addition to reported perivascular locations in the interstitial compartment (18), stem cells also were located on the surfaces of the seminiferous tubules (16,19,20).…”
mentioning
confidence: 73%
“…----+ ----+ ----+ We now know that stem Leydig cells are located both on the tubule surfaces (9,16,19,20) and associated with blood vessels (18,24). In the event of loss of the adult Leydig cells (14,15), stem cells in both locations are capable of regenerating new Leydig cells (16,(20)(21)(22); Fig.…”
Section: Lh -+ ----+ ----+ ---Dbcamp--+ ----+ ----+ --22hc ---+ ----+mentioning
confidence: 99%
“…By following the progressive nature of germ cell loss after busulfan treatment, it is clear that the Sertoli cells are most influenced by post‐meiotic germ cells, with significant changes in Sertoli cell gene transcript levels apparent only when these germ cells are lost from the seminiferous epithelium, ~15–30 days post busulfan injection. Whilst there are also gene expression changes at earlier time points, these are not as widespread suggesting spermatogonia and spermatocytes exert less influence over Sertoli cell gene expression (O'Shaughnessy et al ., 2008b). …”
Section: Germ Cellsmentioning
confidence: 99%
“…The identity of the adult Leydig cell precursor population has been contentious for a number of years with pericytes, peritubular cells, fibroblasts, and endothelial cells all suggested (Jackson et al ., 1986; Kerr et al ., 1987; Teerds et al ., 1990; Davidoff et al ., 2004; O'Shaughnessy et al ., 2008b; Stanley et al ., 2012). Recent data indicates, however, that the major source of adult Leydig cells after EDS treatment are peritubular cells (O'Shaughnessy et al ., 2008b; Stanley et al ., 2012) although a contribution from other sources cannot be ruled out. The role of gonadotrophins in Leydig cell regeneration was established in early EDS studies using hypophysectomised rats or testosterone implants.…”
Section: Leydig Cellsmentioning
confidence: 99%
See 1 more Smart Citation